Assessment of the functional state and physical performance of young men aged 14-16 years in the process of orienteering training - Galan, Y.; Moseichuk, Y.; Kushnir, I.; Lohush, L.; Dotsyuk, L.; Koshura, A.; Potop, V.; Yarmak, O. (Journal of Physical Education and Sport, 2019)
The article presents the results of a pedagogical experiment, which lasted during 2017-2019 academic year. Altogether 69 young men aged 14-16 years (n=69) were involved in the study. According to the purpose of the study, the dynamics of the functional state and physical performance under the influence of orienteering training in the framework of the author's program of physical education classes was analysed. Thus, the developed author`s program for orienteering training in the system of extracurricular work has shown its high efficiency. In the course of the study, the set tasks were implemented, the goal of the study was achieved, and the hypothesis was confirmed.